High-temperature magnetism and microstructure of a semiconducting ferromagnetic (GaSb)1−x(MnSb)x alloy - Oveshnikov, Leonid N.; Nekhaeva, Elena I.; Kochura, Alexey V.; Davydov, Alexander B.; Shakhov, Mikhail A.; Marenkin, Sergey F.; Novodvorskii, Oleg A.; Kuzmenko, Alexander P.; Vasiliev, Alexander L.; Aronzon, Boris A.; Lahderanta, Erkki (Beilstein Journal of Nanotechnology, 2018)
We have studied the properties of relatively thick (about 120 nm) magnetic composite films grown by pulsed laser deposition using the eutectic compound (GaSb)0.59(MnSb)0.41 as target for sputtering. For the studied films we have observed ferromagnetism and an anomalous Hall effect above room temperature, confirming the presence of spin-polarized carriers. Electron microscopy, atomic and magnetic force microscopy results suggest that the films under study have a homogenous columnar structure in the bulk while MnSb inclusions accumulate near the surface. This is in good agreement with the high mobility values of charge carriers. Based on our data we conclude that the magnetic and magnetotransport properties of the films at room temperature are defined by the MnSb inclusions.
Keywords: anomalous Hall effect; high-temperature ferromagnetism; nanostructured materials; thin films